Peran Pidana Pengawasan Sebagai Alternatif Pemidanaan Dalam Mewujudkan Tujuan Pemidanaan Di Indonesia - Amelia Suci Rahmadani; Tenti Ayu; Yulia Tri Wahyuni; Cahaya Dwi Anggola; Ria Anggraeni Utami (GLOBAL SCIENTS PUBLISHER, 2026)
Supervisory punishment is one of the alternative sanctions developed in the Indonesian criminal law system as an effort to reduce dependence on imprisonment, especially in addressing the problem of prison overcrowding. This study aims to examine the role of supervisory punishment as an alternative sanction and to assess its effectiveness in achieving the objectives of criminal sanctions, which include aspects of prevention, rehabilitation, and community protection. The method used is normative legal research with statutory and conceptual approaches, through a study of Law Number 1 of 2023 concerning the Criminal Code and related legal literature. Research results show that supervisory punishment plays an important role in reducing the number of inmates in correctional institutions, thereby helping to address overcapacity. In addition, this type of punishment provides opportunities for offenders to remain in the community under certain supervision, making the rehabilitation process more effective. From the perspective of the objectives of punishment, supervisory punishment is considered capable of preventing the recurrence of criminal acts, supporting the improvement of offenders' behavior, and still providing protection to society. However, in its implementation, there are still obstacles, including the limitations of supervisory officers, the suboptimal supervision system, and public views that still emphasize imprisonment.